Factors Influencing Leaf Chlorophyll Content in Natural Forests at the Biome Scale - Li, Ying; He, Nianpeng; Hou, Jihua; Xu, Li; Liu, Congcong; Zhang, Jiahui; Wang, Qiufeng; Zhang, Ximin; Wu, Xiuqin (Frontiers in Ecology and Evolution, 2018)
Chlorophyll (Chl) is an important photosynthetic pigment to the plant, largely determining photosynthetic capacity and hence plant growth. However, this concept has not been verified in natural forests, especially at a large scale. Furthermore, how Chl varies in natural forests remains unclear. In this study, the leaves of 823 plant species were collected from nine typical forest communities, extending from cold-temperate to tropical zones in China, to determine the main factors influencing leaf chlorophyll content in different regions and at different scales. We measured chlorophyll a (Chl a), chlorophyll b (Chl b), Chl (Chl a+ Chl b), and the ratio of Chl a and Chl b (Chl a/b). The results showed that Chl a, Chl b, and Chl a/b values were in the range of 0.87–15.92 mg g–1 (mean: 4.18 mg g–1), 0.32–6.42 mg g–1 (mean 1.72 mg g–1), and 1.43–7.07 (mean: 2.47). The values of these three Chl parameters significantly differed among plant functional groups (trees < shrubs < herbs, coniferous trees < broadleaved trees, and evergreens < deciduous trees). Unexpectedly, Chl a, Chl b, and Chl a+b increased slightly with increasing latitude. Climate, soil, and phylogeny exert only a small effect on the spatial variation of Chl in natural forests, with large variation in the Chl of coexisting species masking the spatial patterns. This study is the first to report variations in Chl among different types of natural forests at a large scale, demonstrating that the fuzzy regulation of Chl makes it very difficult to take Chl as the main input parameter to the models of natural forests.